Active packaging based on swim bladder gelatin/galangal root oil nanofibers: Preparation, properties and antibacterial application. (December 2020) - Zhou, Changqian; Abdel-Samie, Mohamed A.; Li, Changzhu; Cui, Haiying; Lin, Lin
Highlights: Swim bladder gelatin/galangal root oil nanofiber was prepared by electrospinning. Amino acid composition affected the fiber-forming properties of fish gelatin. The sustained release of GRO from nanofiber explained its high antimicrobial activity. The nanofiber mats delayed microbial growth and extended the shelf life of beef. Abstract: In this work, swim bladder gelatin (SBG) nanofibers incorporating galangal root oil/ β -cyclodextrin (GRO/ β -CD) were fabricated by electrospinning for antibacterial packaging use. SBG exhibits desirable fiber-forming properties due to its unique amino acid composition. Specifically, β -CD played an essential role in preventing GRO volatilization by forming GRO/ β -CD inclusion complex during electrospinning. FTIR and XRD results confirmed that GRO was successfully encapsulated in the β -CD cavity through the process assisted with ultrasound. Besides, the hydrogen bonding interactions were major forces both in inclusion complex and nanofibers, which enhanced the thermal stability. The release kinetic curve demonstrated that the release mechanism of GRO from nanofibers was subject to Fickian diffusion. In the application experiment, the prepared nanofiber mats showed efficient inhibitory effect against EHEC O157, and little influence on the sensory properties of beef. Our findings provided a feasible strategy to explore application potential of natural antibacterial substances in active food packaging.